Unraveling the Basis of Neonicotinoid Resistance in Whitefly Species Complex: Role of Endosymbiotic Bacteria and Insecticide Resistance Genes - Barman, Mritunjoy; Samanta, Snigdha; Upadhyaya, Gouranga; Thakur, Himanshu; Chakraborty, Swati; Samanta, Arunava; Tarafdar, Jayanta (Frontiers in Microbiology, 2022)
Bemisia tabaci (whitefly) is one of the most detrimental agricultural insect pest and vectors of many plant viruses, distributed worldwide. Knowledge of distribution pattern and insecticide resistance of this cryptic species is crucial for its management. In this study, genetic variation of mitochondrial cytochrome oxidase subunit 1 (MtCoI) gene of B. tabaci was analysed followed by a study of infection profile of various endosymbionts in 26 whitefly population collected from West Bengal, India. Phylogenetic analysis revealed Asia I as the major cryptic species (65.38%) followed by Asia II 5, China 3, and Asia II 7, which was diversified into 20 different haplotypes. In addition to the primary endosymbiont (C. poriera), each of the four whitefly species showed variable population of three secondary endosymbionts, majorly Arsenophonus with the highest infection rate (73.07%) followed by Wolbachia and Rickettsia. Further phylogenetic analyses revealed presence of two subgroups of Arsenophonus, viz., A1 and A2 and one each in Wolbachia (W1) and Rickettsia (R3). Resistance to thiamethoxam, imidacloprid and acetamiprid insecticides were analysed for a clear picture of pesticide resistance status. Highest susceptibility was noted towards thiamethoxam (LC50= 5.36 mg/L) followed by imidacloprid and acetamiprid. The whitefly population from Purulia and Hooghly districts bearing Asia II 7 and Asia II 5 cryptic species respectively depicts maximum resistance. The differences in mean relative titre of four symbiotic bacteria among field populations varied considerably, however, a significant positive linear correlation was observed between the resistance level and relative titre of Arsenophonus and Wolbachia in case of imidacloprid and thiamethoxam, while only Wolbachia was found in case of acetamiprid. Expression analysis demonstrated differential upregulation of insecticide resistance genes with Purulia and Hooghly population showing maximally upregulated P450 genes. Moreover, thiamethoxam and imidacloprid resistance ratio (RR) showed significant correlation with CYP6CM1, CYP6DZ7 and CYP4C64 genes, while acetamiprid RR correlated with CYP6CX1, CYP6DW2, CYP6DZ7 and CYP4C64 genes. Taken together, these findings suggested P450 mono-oxygenase and symbiotic bacteria together affected whitefly resistance to neonicotinoids. Hence, symbiont-oriented management programme could be a better alternative to control or delay resistance development in whitefly and can be used for pesticide clean-up in agricultural field.